2010
DOI: 10.1111/j.1574-6941.2009.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation ofN-acyl-homoserine lactone production and degradation inPseudomonas putidaIsoF

Abstract: The biocontrol strain Pseudomonas putida IsoF, which was isolated from a tomato rhizosphere, is a known N-acyl-homoserine lactone (AHL) producer with only one LuxI/LuxR-like quorum-sensing (QS) system. The production and degradation of AHLs were analysed in different growth phases of the bacterium. Using the analytical tools of ultra performance liquid chromatography and high resolution MS, it was possible to determine not only the various AHLs synthesized over time but also their degradation products. 3-oxo-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 60 publications
7
86
0
1
Order By: Relevance
“…AI-2 is an unavoidable waste product of an essential metabolic pathway in many bacteria. Interestingly, a similar AI dynamic is observed during the growth of P. putida IsoF, although its AI (mainly 3-oxo-decanoyl-homoserine lactone) is not known to be a waste product (105). Due to different stabilities of AIs and some AIreceptor complexes, actual AI concentrations may either reflect more the actual population (for unstable AIs) or integrate information over several generations (for stable AIs).…”
Section: Variability Of the Ai Production Rate: The Hybrid Push-pull mentioning
confidence: 74%
See 1 more Smart Citation
“…AI-2 is an unavoidable waste product of an essential metabolic pathway in many bacteria. Interestingly, a similar AI dynamic is observed during the growth of P. putida IsoF, although its AI (mainly 3-oxo-decanoyl-homoserine lactone) is not known to be a waste product (105). Due to different stabilities of AIs and some AIreceptor complexes, actual AI concentrations may either reflect more the actual population (for unstable AIs) or integrate information over several generations (for stable AIs).…”
Section: Variability Of the Ai Production Rate: The Hybrid Push-pull mentioning
confidence: 74%
“…AI induces the transcription of RsaL and QteE (76) and activates QscR as a ligand (104). Furthermore, AI levels may be controlled by self-produced AI-degrading enzymes (105). In Vibrio fischeri, the expression of the AI receptor LuxR is upregulated at intermediary but downregulated at high AI concentrations, which was assumed to maintain light production within a certain strength range (106).…”
Section: Role Of Ai Systems and Accessory Mechanisms In Homeostasis Omentioning
confidence: 99%
“…Aybey and E. Demirkan (Fekete et al, 2010). It has been reported that signal molecules are produced maximally when cultures reach the late stationary phase of growth (Gallagher et al, 2002; Lépine et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Bars show the mean¡SEM (n53 independent experiments) with statistical differences at P,0.05 and P,0.01 indicated by * and **, respectively. Journal of Medical Microbiology 65 (Fekete et al, 2010). It has been reported that signal molecules are produced maximally when cultures reach the late stationary phase of growth (Gallagher et al, 2002;Lépine et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several model approaches have also been proposed for Pseudomonas putida, in closed systems (batch) as well as in continuous cultures (chemostat) [16][17][18]. The goal of this manuscript is to review such models, investigating mathematical properties and principles underlying the equations.…”
Section: Introductionmentioning
confidence: 99%